Penggunaan Game (Wordwall) Dalam Mata Kuliah Matematika Informatika Bagi Mahasiswa Jurusan Teknik Elektro - Yesaya, Mey Chyntia; Persulessy, Sylvia Irene (Scholars: Jurnal Sosial Humaniora dan Pendidikan, 2023)
Advances in technology have proliferated in this global world, not only in big cities but also in small towns. In the last 10 years, electronic games or so-called online games have proliferated. There's a lot of game centers popping up. The game center itself is not like an Internet cafe, they have more regulars than any cafes. This is what makes the game center almost always bustling with visitors. Online games also have a major impact on the development of both the child and the soul of the individual, which dominates the online game playing by students. The purpose of this study is to know the enormous impact online games have on learning to improve the study of student electrical engineering at ambon state. The result of this research is that 88 % of students are very active in multiplation and are particularly enthusiastic when playing the infomratika math game created through word word online media. This can encourage their curiosity when a game is not finished and tend to be keen to try it at all times. It is this curious nature that will change their interest in learning, so that their study too will increase. With such a learning method expected to enhance student math achievement.Keywords: game, learning outcomes, mathematics, Wordwall